2016
DOI: 10.1007/s10147-016-1015-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of synchronous colorectal cancer in patients with esophageal cancer: an analysis of 480 consecutive colonoscopies before surgery

Abstract: The results of the present study suggested that pretreatment screening with total colonoscopy is meaningful for patients with esophageal cancer, because the frequency of synchronous colorectal cancer was not negligible. Particularly, in patients >70 years and with history of heavy smoking, pretreatment colonoscopy might be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The concept of ‘field cancerization’ is postulated to predispose patients to synchronous tumors whereby shared risk factors cause tumors that are spatially separated, such as smoking for lung cancer. Similarly, synchronous esophageal and colon cancers occurring at an incidence of 2.9%, share the risk factors of smoking and alcohol intake, and the protective factor of vegetable and fruit intake [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ‘field cancerization’ is postulated to predispose patients to synchronous tumors whereby shared risk factors cause tumors that are spatially separated, such as smoking for lung cancer. Similarly, synchronous esophageal and colon cancers occurring at an incidence of 2.9%, share the risk factors of smoking and alcohol intake, and the protective factor of vegetable and fruit intake [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed major potential variables related to the detection rate, such as risk factors for tumorous lesions (body mass index, smoking status, drinking status, and regular aspirin use). (28)(29)(30)(31)(32)(33) Additionally, the endoscopic setting was associated with the detection rate of neoplasms. For instance, suppression of peristalsis by L-Menthol reportedly indicates a higher adenoma detection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple primary malignant tumors (MPMTs) refers to two or more primary malignant tumors in the same individual. 1 MPMTs may be synchronous or metachronous. The majority of MPMTs that occur in multiple organs are metachronous, while the presence of synchronous MPMTs (sMPMTs) is less common.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of MPMTs that occur in multiple organs are metachronous, while the presence of synchronous MPMTs (sMPMTs) is less common. Although it has been reported that special attention should be given to MPMTs, especially for head, neck, and urinary tumors, 1 their prevalence is generally very low. Only sporadic cases have been reported concerning multiple myeloma (MM) with sMPMTs.…”
Section: Introductionmentioning
confidence: 99%